Perfil dos Transportes Aeromédicos de Pacientes Críticos do Sistema Único de Saúde em Minas Gerais - Vânia Paula de Carvalho (2019)
The aeromedical transport of critical patients is a frequent reality, it is an important complement to the terrestrial transport and it is an alternative to cover the vacancies of tertiary care. The State of Minas Gerais, located in the Southeast Region, has large territorial dimensions and the largest number of municipalities in Brazil. The objective of this study was to analyze the epidemiological profile of intra-hospital aeromedical transport performed by a outsourced service to SUS-MG critical patients between November 2012 and December 2017. The data from this research came from a private company that was outsourced, to attend users to the Unified Health System of Minas Gerais (SUS-MG). The population consisted of 702 critical patients, who required interhospital air transport. It is a quantitative research, with an observational and descriptive character. The data collected were stored in Excel® spreadsheets and the software used in the analyzes was R, version 3.6.0, (R Core Team, 2019); IBM SSPSS, version 20.0 (IBM Corp. Released 2011), and MiniTab, version 18.0 (MiniTab, Inc. 2000). Categorical variables were presented as absolute and relative frequencies. For the continuous variables, position measurements (mean, median, quartile 1 and quartile 3, minimum and maximum) and dispersion measurements (standard deviation and coefficient of variation) were determined. Mapped maps with aerial geo-referencing and maps with the Meso-regions of the State with the cities of origin and destination. The results found were: the North Macroregion was the one that demanded the transportation to tertiary health centers (23.1%). The Metropolitan Region received the most critical patients (509 / 72.5%), mostly for neonatal ICUs. The transport in the aircraft wing fixed were prevalent (701 / 99.8%). The majority of those attended were male (56.6%); in the neonatal age group (37.0%); body weight with median up to 10 years of age of 3.2 kg and above 10 years of 70.7 kg. The majority of patients had peripheral venous access (59.1%); 'cardiological / cardiovascular' diagnostic classification up to 10 years of age (45.0%) and 'trauma' up to 10 years of age (40.1%); in mechanical ventilation (51.7%), oxygen use (89%) and FiO² up to 50% (68.0%). Of the 95 transports categorized as 'trauma', with TBI (28.4%), the majority in the age group over 10 years old (85.2%) and classified as severe TBI (51.9%). The median distance to the destination city was 336.5 km and the most frequent base takeoff times were in the morning.